Ο Εφέσου Χρυσόστομος για την καταστροφή της Σμύρνης - Σολομωνίδου Βικτώρια (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1983)
The destruction of Smyrna by fire in September 1922 was the last in a series of events which culminated in the ousting of the Greek populations from Asia Minor. To its larger part, the course of these events is well-known: By the end of August 1922, most of the Christian populations from the interior of Asia Minor had followed the Greek army in its retreat towards Smyrna and, as a result, a substantial number of refugees had gathered in the city waiting in vain for ships to carry them to the neighbouring islands. With the departure of the Greek officials on 8 September, the countdown for Giaour Izmir had begun. The next day, the Turkish army occupied the city and the celebrations of the local Turks culminated on 11 September when M. Kemal himself came to the city. On the same day, Chrysostom, the Metropolitan of Smyrna, was lynched by the mob and, after a long series of looting, murders, pillage, and rapes the city was set to flames on 13 September. This article sets the background to a report addressed by the Metropolitan of Ephessos Chrysostomos Hadjistavrou to the Patriarchate in early October 1922. The report, which is published here annotated, describes in detail the last days of Smyrna and provides information as to the fate of neighbouring Greek communities and their religious leaders. It also refers to the arrival of the refugees in Greece and the measures taken for their relief. Metropolitan Chrysostomos Hadjistavrou was born in Aidin (1880) and studied at Chalki and Lausanne. He was a close associate of Metropolitan Chrysostom of Smyrna with whom he worked for the relief and encouragement of the Greek populations throughout the 1909-1919 persecutions. In 1962 he became Archbishop of Athens, a post which he kept until 1967 when he was forced into retirement by the military regime.